Tinjauan Pelaksanaan Analisis Rekam Medis di Bangsal Anak - Nikmah Ayu Ramadhani Amir; Sri Lestari (SENTRI: Jurnal Riset Ilmiah, 2025)
Medical records are important documents that contain patient identification, examination results, treatments, procedures, and services provided during care. The completeness and consistency of medical record documentation serve as a crucial source of information for hospital management in evaluating and improving the quality of healthcare services. This study aims to review the implementation of medical record analysis in the pediatric ward. A qualitative descriptive method was employed, utilizing data collection techniques that included interviews and observations. Interviews were conducted with medical record analysis staff and the deputy head of the pediatric ward. At the same time, observations were carried out using a checklist on 10 patient medical record files from the pediatric ward in December 2024. The results showed that the implementation of medical record analysis in the pediatric ward was conducted only quantitatively, while qualitative analysis had never been performed. The components of important report completeness and documentation showed a 100% completeness rate. However, in the patient identification section, specifically in gender, and in the authentication section for the nurse’s name, some forms were incomplete, resulting in an overall completeness rate of only 97.5%. The main obstacle in the implementation of the analysis was the transition process from manual medical records to electronic medical records, which required staff to conduct dual quantitative analyses in both formats.